1971
DOI: 10.1901/jaba.1971.4-191
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF SELF‐RECORDING ON THE CLASSROOM BEHAVIOR OF TWO EIGHTH‐GRADE STUDENTS1

Abstract: The effects of self-recording on classroom behavior of two junior high school students was investigated. In the first experiment, study behavior of an eighth-grade girl in history class was recorded. Following baseline observations her counselor provided slips for the girl to record whether or not she studied in class. This resulted in an increase in study. When slips were withdrawn, study decreased and then increased once self-recording was reinstated. After teacher praise for study was increased, self-record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
2
2

Year Published

1973
1973
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(104 citation statements)
references
References 11 publications
2
98
2
2
Order By: Relevance
“…For instance, the manager may give himself an extra coffee break for having a clean desk the preceding day or stay after work for a half hour for each day that the paperwork is not taken care of. A number of studies in educational and clinical psychology have clearly demonstrated the effectiveness of self-recording, self-reward, and self-punishment [Bucher & Fabricatore, 1970;Broden, Hall, & Mitts, 1971;Johnson & White, 1971;Bolstad & Johnson, 1972;Flannery, 1972;Sobell & Sobell, 1973;Axelrod, Hall, Weiss, & Rohrer, 1974] and our own work has shown that it works in a managerial setting .…”
Section: Social Learning Theory In Perspectivementioning
confidence: 73%
“…For instance, the manager may give himself an extra coffee break for having a clean desk the preceding day or stay after work for a half hour for each day that the paperwork is not taken care of. A number of studies in educational and clinical psychology have clearly demonstrated the effectiveness of self-recording, self-reward, and self-punishment [Bucher & Fabricatore, 1970;Broden, Hall, & Mitts, 1971;Johnson & White, 1971;Bolstad & Johnson, 1972;Flannery, 1972;Sobell & Sobell, 1973;Axelrod, Hall, Weiss, & Rohrer, 1974] and our own work has shown that it works in a managerial setting .…”
Section: Social Learning Theory In Perspectivementioning
confidence: 73%
“…Individual means of the percentage of reinforcement taken by the eight children for the entire behavioral self-control phase 1 are compared with the mean percentages of on-task behavior for the same period in Table 2 Broden, et al, (1971) suggestion that selfrecording procedures are more effective if they are used in conjunction with established reinforcement techniques. Other research has investigated such factors as prior learning (Kanfer and Marston, 1963) the influence of models (Bandura and Whalen, 1966;Bandura, Grusec, and Menlove, 1967;McMains and Liebert, 1968), the effects of rule structure and training method (Liebert, Honratty, and Hill, 1969) on the accuracy of self-assessment, self-recording, and self-determination of reinforcement, but none of these studies has been conducted in classroom settings nor have they employed a functional analysis of behavior as a frame of reference.…”
Section: Reliability Of Observationsmentioning
confidence: 99%
“…The Glynn study left open the question as to whether behavioral selfcontrol procedures would be effective with populations other than grade-nine girls, (e.g., younger children). Broden, Hall, and Mitts (1971) used self-recording procedures in classroom settings to increase study behavior in an eighth-grade girl and to decrease talk-outs in an eighth-grade boy. It was suggested that selfrecording procedures would be most effective if they were used in conjunction with established reinforcement techniques such as teacher praise and tokens.…”
mentioning
confidence: 99%
“…High reliability for selfreports of smoking behavior (Powell and Azrin, 1968;Thompson and Wilson, 1966) and selfmedicating behavior (Azrin and Powell, 1969) have been reported. Broden, Hall, and Mitts (1971) found low reliability for day-to-day variations in studying behavior and talking-out behaviors. Fixsen, Phillips, and Wolf (1972) Kazdin (in press).…”
Section: Reliabilitymentioning
confidence: 99%
“…However, several studies have suggested that when such procedures are used, the act of recording itself may be an independent variable (McFall, 1970;Stunkard, 1970). Broden, Hall, and Mitts (1971), as well as Johnson, Martin, and White (1970), found that recording the amount of time spend on studying or other academic work increased performance with no other scheduled consequences. Sluyter and Hawkins (1972), however, suggested that with some students, concrete reinforcers, rather than feedback or social reinforcement alone, may be important in producing scholastic improvement via contingency contracting.…”
mentioning
confidence: 89%